2017
DOI: 10.1038/s41598-017-03907-2
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of phytohormone dynamics during combined drought and pathogen stress in Arabidopsis thaliana reveals ABA and JA as major regulators

Abstract: Global transcriptome studies demonstrated the existence of unique plant responses under combined stress which are otherwise not seen during individual stresses. In order to combat combined stress plants use signaling pathways and ‘cross talk’ mediated by hormones involved in stress and growth related processes. However, interactions among hormones’ pathways in combined stressed plants are not yet known. Here we studied dynamics of different hormones under individual and combined drought and pathogen infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 82 publications
2
60
1
Order By: Relevance
“…The pellet was washed with 80% acetonitrile containing 1% acetic acid and the resulting supernatant was mixed with the first supernatant. Finally, the supernatants were successively pre-treated and their IAA contents were determined as described previously (Gupta et al, 2017).…”
Section: Quantification Of Iaamentioning
confidence: 99%
“…The pellet was washed with 80% acetonitrile containing 1% acetic acid and the resulting supernatant was mixed with the first supernatant. Finally, the supernatants were successively pre-treated and their IAA contents were determined as described previously (Gupta et al, 2017).…”
Section: Quantification Of Iaamentioning
confidence: 99%
“…However, increased ABA levels are associated with enhanced susceptibility to Pst DC3000 in Arabidopsis at the post-invasive stage (de Torres-Zabala et al, 2007). Interestingly, when Arabidopsis plants are challenged with drought and pathogen simultaneously, ABA level remains unchanged but the levels of defense hormones SA and JA are raised, providing an explanation for why the combined stress leads to enhanced disease resistance in Arabidopsis (Gupta et al, 2017). In addition, drought-stressed chickpea exhibits higher resistance to a xylem-inhabiting bacterial pathogen, Ralstonia solanacearum (Sinha et al, 2016).…”
Section: Effect Of Drought On Plant Resistancementioning
confidence: 99%
“…Interestingly, several ABA‐related genes, including NCED3 , were found to be down‐regulated in C. sinensis NHR to Xcv , and this was also associated with a strong decrease in ABA levels at early times post‐inoculation (Petrocelli et al ., ). In Arabidopsis and rice, several reports have shown that ABA accumulation induced by bacterial pathogens promotes susceptibility via the suppression of the accumulation of phenolic compounds through phenylalanine ammonia‐lyase (PAL) inhibition, callose deposition and also SA‐mediated defences, contributing to symptom development (Gupta et al ., ; Lievens et al ., ; de Torres Zabala et al ., ; Xu et al ., ). However, ABA can also positively influence disease resistance by regulating stomatal closure (Lim et al ., ).…”
Section: Discussionmentioning
confidence: 98%